2021
DOI: 10.3390/antiox10122026
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spot Biomarkers of Oxidative Stress and Inflammation Associated with Blood Pressure in Rural Senegalese Women with Incident Hypertension

Abstract: Blood biomarkers of oxidative stress and inflammation have been associated with increased risk of hypertension development; yet their application in sub-Saharan Africa has been limited due to the lack of blood collection facilities. In this study, we evaluated the usefulness of dried blood spots (DBS), a more feasible alternative to venous blood, in rural sub-Saharan residents. We recruited 342 women with incident hypertension from rural Senegal, and measured C-reactive protein (CRP) and malondialdehyde (MDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The findings highlight the superiority of FPG or FBG as the most potent predictor of diabetes, surpassing the predictive capability of BMI. Of relevance to this revelation are reports [ 113 , [127] , [128] , [129] , [130] , [131] ] who revealed better diabetes prediction outcomes with FPG than other metrics. Furthermore, research shows that higher blood glucose drives diabetes risk than other metrics across all ages, sex and ethnicities [ 132 , 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings highlight the superiority of FPG or FBG as the most potent predictor of diabetes, surpassing the predictive capability of BMI. Of relevance to this revelation are reports [ 113 , [127] , [128] , [129] , [130] , [131] ] who revealed better diabetes prediction outcomes with FPG than other metrics. Furthermore, research shows that higher blood glucose drives diabetes risk than other metrics across all ages, sex and ethnicities [ 132 , 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…in 1991 in patients with cystic fibrosis 14 . Since then, several studies 15,16 have concluded that CRP is accurately detectable from DBS and other groups [17][18][19][20] have implemented this in diverse research fields on small scale. However, to date, there is no evidence that CRP from DBS can be used in everyday diagnostic practice.…”
mentioning
confidence: 99%
“…Our Special Issue presents innovative research [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and review [ 13 , 14 , 15 ] papers addressing many of these questions related to the fundamental OS involvement in the onset and progression of several acute and chronic diseases, and about the correlated biomarkers and potential therapies. Precisely, the 12 research articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] included in this Special Issue are focused on evidencing the OS role in diagnostics, signatures of the disease course, molecules involved, OS potential treatments and effects, and short- and long-term consequences.…”
mentioning
confidence: 99%
“…Our Special Issue presents innovative research [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and review [ 13 , 14 , 15 ] papers addressing many of these questions related to the fundamental OS involvement in the onset and progression of several acute and chronic diseases, and about the correlated biomarkers and potential therapies. Precisely, the 12 research articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] included in this Special Issue are focused on evidencing the OS role in diagnostics, signatures of the disease course, molecules involved, OS potential treatments and effects, and short- and long-term consequences. Precisely, Chen et al [ 1 ], by performing a nano-electrospray ionization–mass spectrometry (nanoESI-MS)-based lipidomic profiling study on lipid accumulation and oxidation in kidney cells in the chronic kidney disease (CKD) model, confirmed the key role of OS and lipid dysregulation in renal lipid droplet (LD) alteration at the molecular level.…”
mentioning
confidence: 99%
See 1 more Smart Citation